Pollen grain morphology is not exclusively responsible for pollen collectability in bumble bees - Konzmann, Sabine (Sci Rep, 2019)
Bee-pollinated plants face a dilemma in that bees both passively transport pollen grains among conspecific flowers and actively collect pollen to feed their larvae. Therefore, mechanisms that reduce pollen collection by bees have evolved in melittophilous plants. Malvaceae pollen is uncollectable for corbiculate bees which has previously been ascribed to pollen size, spines, and pollenkitt. We analysed the influence of pollen grain properties (diameter, spine length, spine density) on the collectability of echinate (spiny) pollen by bumble bees (Bombus terrestris). Workers individually foraging on one of eight plant species from six families performed significantly less pollen foraging on plants which have large, echinate pollen grains. Nevertheless, neither pollen grain size, spine length, nor spine density prove to be an absolute disqualifier for collectability. While pollen foragers did not shift to nectar collection but seized visiting flowers with uncollectable pollen, nectar foragers performed regular foraging bouts on these plants. Pollen that is uncollectable for corbiculate bees limits pollen depletion by generalist bumble bees and probably also honey bees while maintaining them as pollinators, which is an effective solution to the pollen dilemma. As previous assumptions about the impact of pollen morphology on its collectability are disproved, potentially determining factors are discussed.